Expression of angiogenic markers in murine schistosomiasis mansoni - Botelho, Mónica (2018)
Background: Schistosomiasis is associated immunologic reactions to Schistosoma eggs trapped in tissues. Antigens released from the egg stimulate a granulomatous reaction involving lymphocytes, macrophages and eosinophils that results in clinical disease. Schistosomose is considered the second most devastating parasitic disease after malaria in the world. Its etiological agents are related to the carcinogenic process in the bladder and fibrosis in the liver. Recent advances in the fields of molecular biology and epidemiology have led to significant revelations to clarify the relationship between infectious agents and cancer and have given valuable insights into the molecular basis of carcinogenesis. Aims: Furthermore, to better understand these mechanisms, we evaluated the role of inflammation (IL-6), angiogenesis (CD31), lymphangiogenesis (LYVE-1) and carbohydrate metabolism in an animal model infected with S. mansoni eggs through histochemical, histoenzymological, and immunohistochemical approaches. Results: The results obtained in this study indicate that schistosomiasis influences the release of proinflammatory factors like IL-6 in significant amounts in the liver, which may be related to the amount of granulomas obtained in tissue histological analysis. Angiogenesis was increased in infected mice. Microvessel Density (MVD) is also increased. The expression of LYVE-1 in liver and spleen indicated an increase in lymphangiogenesis when compared to controls. Schistosoma eggs presented large amounts of fibrotic tissue and promoted a significant decrease of glycogen in the infected tissue. Conclusions: Infection caused by eggs of S. mansoni increases inflammation, lymph/angiogenesis and influences cellular metabolic processes for the maintenance and / or development of the parasite, and for a cellular repair response, where neovascularization promotes these pathways.